Usability assessment of Versius, a new robot-assisted surgical device for use in minimal access surgery. Issue 1 (24th May 2020) - Haig, Fiona; Medeiros, Ana Cristina Barbosa; Chitty, Karen; Slack, Mark
Abstract : Objectives: Versius is a teleoperated surgical robotic system intended for use in minimal access surgery. This study aimed to validate the safety and effectiveness of the Versius user interface in the hands of trained users and identify and address the causes of any user errors. Design: Surgical teams completed a commercially representative training program over 3.5 days. After training was completed, the usability-related aspects of the system were assessed. Setting: A simulated operating room using a cadaveric model. Participants: Surgical teams consisting of a lead surgeon, assistant surgeon, scrub nurse and circulating nurse. Main outcome measures: Usability-related aspects of the system were assessed through the completion of critical and non-critical tasks. A critical task was defined according to the Food and Drug Administration's definition, as a user task which, if performed incorrectly or not performed at all, would or could cause serious harm to the patient or user, where harm is defined to include compromised medical care. Results: In total, 17 surgical teams participated in the study and all were experienced in laparoscopic surgery. The number of robotic surgeries performed by the participants per month ranged from 0 to 100. Surgical specialties were similarly represented from obstetrics and gynecology, colorectal, urology and upper gastrointestinal. No critical task failures were observed. Of all the tasks completed, 98% were recorded as a pass or a pass with difficulty. Conclusions: These results demonstrate that in a simulated clinical setting, Versius can be safely used by both laparoscopically and robotically trained healthcare professionals. These results support the progression to assessment of Versius in preclinical studies.